Urgensi Kriminalisasi Pengguna Jasa Prostitusi di Indonesia - Andrew Ramadhani; Hervina Puspitosari (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Prostitution is a crime that not only injures legal norms, but the whole norm is also injured, starting from religious norms, decency, and decency. The number of cases of prostitution in Indonesia is increasing. There are 3 (three) interrelated subjects in the practice of prostitution, namely service users, service providers or commercial sex workers (PSK) and pimps. The Criminal Code (KUHP) actually only regulates the threat of punishment for prostitution against the pimp, does not regulate the threat of punishment against users of prostitution services. Based on this, this research needs to explore criminal law policies against users of prostitution services in Indonesia as well as the urgency of their criminalization. The research methodology is normative, with a statutory and conceptual approach. Data collection was obtained by means of library research and interviews by taking samples at the Surabaya District Attorney. The results of the study indicate that criminal law policies against prostitution service users in Indonesia are contained in Regional Regulations (perda) which only exist in a few areas, namely the City of Surabaya, Jakarta and Bumbu Regency, South Kalimantan Province, which regulates punishments in the form of imprisonment/fines/ returned to his family. The inconsistency of the sentencing rules is certainly very confusing and the punishment is also not a deterrent. Cases of prostitution in Indonesia if you look at the side of the Criminal Code, of course it is difficult to reduce it if you only criminalize the pimps and allow users of prostitution services which are actually the root cause of the practice of prostitution. If there are no prostitution service users, then there are no pimps and service providers either. Users of prostitution services in Indonesia are therefore obliged to be eradicated by criminalizing them.